Manipulating behaviour with substrate‐borne vibrations – potential for insect pest control. Issue 1 (16th July 2014) - Polajnar, Jernej; Eriksson, Anna; Lucchi, Andrea; Anfora, Gianfranco; Virant‐Doberlet, Meta; Mazzoni, Valerio
Abstract This review presents an overview of the potential use of substrate‐borne vibrations for the purpose of achieving insect pest control in the context of integrated pest management. Although the importance of mechanical vibrations in the life of insects has been fairly well established, the effect of substrate‐borne vibrations has historically been understudied, in contrast to sound sensu stricto. Consequently, the idea of using substrate‐borne vibrations for pest control is still in its infancy. This review therefore focuses on the theoretical background, using it to highlight potential applications in a field environment, and lists the few preliminary studies that have been or are being performed. Conceptual similarities to the use of sound, as well as limitations inherent in this approach, are also noted. © 2014 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.